PENGARUH EFIKASI DIRI DAN MOTIVASI TERHADAP MINAT BERWIRAUSAHA MAHASISWA UNIVERSITAS MAHAKARYA ASIA YOGYAKARTA (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2025)
Entrepreneurship education plays a significant role in shaping entrepreneurial interest and skills among students. However, other factors also influence entrepreneurial interest, namely self-efficacy and motivation. The aim of this study is to determine the influence of self-efficacy and motivation on entrepreneurial interest in students at Mahakarya Asia University, both partially and simultaneously. This study used a quantitative approach with a population of Mahakarya Asia University students at the PSKU Yogyakarta campus. The sampling technique used was convenience sampling, with a total of 180 students as respondents. Data analysis was carried out through instrument testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing using the t-test, F-test, and coefficient of determination test, with the assistance of SPSS software 25. The results of the study show that Self-Efficacy gets a significant value of 0.000
Keywords: Self-Efficacy; Motivation; Interest in Entrepreneurship.